Fast solution of Cahn-Hilliard variational inequalities using implicit time discretization and finite elements - Bosch, J; Stoll, M; Benner, P (2012)
We consider the ecient solution of the Cahn-Hilliard variational inequality using an implicit time discretization, which is formulated as an optimal control problem with pointwise constraints on the control. By applying a semi-smooth Newton method combined with a Moreau-Yosida regularization technique for handling the control constraints we show superlinear convergence in function space. At the heart of this method lies the solution of large and sparse linear systems for which we propose the use of preconditioned Krylov subspace solvers using an eective Schur complement approximation. Numerical results illustrate the competitiveness of this approach.